Implementation of regional regulation number 3 of 2023 concerning the protection of women and children in East Bolaang Mongondow Regency - Pangalima, Mohamad Iksan; Mamonto, Fitri; Tarore, Steven (Technium Social Sciences Journal, 2024)
This study aims to determine, analyze and interpret the implementation and inhibiting factors of the implementation of Regional Regulation Number 3 of 2023 concerning the Protection of Women and Children in East Bolaang Mongondow Regency. This type of research is descriptive with a qualitative approach based on the results of observations and interviews. This research analysis uses the concept of public policy implementation of George C. Edward III. The results showed several things, namely (a) the support of regional apparatus was very optimal; (b) the form of commitment and cooperation of vertical agencies was carried out through a Memorandum of Understanding (MoU); (c) the stipulation of Regional Regulation Number 3 of 2023 proves the alignment of the local government to be present in the midst of society, and play an active role in implementing the protection of women and children; (d) budget shortages do not affect the socialization of prevention in the field, and are not significant with the increase in cases of violence against women and children; (e) supporting infrastructure for reunification at the Regional Technical Implementation Unit (UPTD) is very limited, as well as other facilities such as office buildings are also not yet available; and (f) existing resources are not yet optimal, and professional staff are still needed. The main inhibiting factors for implementing this regulation are resources in the context of human resources (staff) where professional personnel are still needed in the field of empowerment and case handling and equipment resources (facilities) where facilities are still needed in the form of office buildings and safe houses for the operationalization of the implementation of this regulation.